Camptothecin suppresses NRF2–ARE activity and sensitises hepatocellular carcinoma cells to anticancer drugs - Chen, Feng (Br J Cancer, 2017)
BACKGROUND: Resistance to chemotherapy is a major obstacle in the treatment of human hepatocellular carcinoma (HCC). Despite playing an important role in chemoprevention, nuclear factor erythroid 2-related factor 2 (NRF2) also contributes to chemo- and radio-resistance. The current study focusses on camptothecin as a novel NRF2 inhibitor to sensitise HCC to chemotherapy. METHODS: The expression and transcriptional activity of NRF2 in human HCC biopsies and camptothecin-treated culture cells were determined using immunostaining, western blot, reverse-transcription quantitative real-time PCR (RT–qPCR) and luciferase reporter assay. The effect of camptothecin on chemosensitivity of cancer cells was assessed in vitro and in xenografts. RESULTS: The expression and transcriptional activity of NRF2 were substantially elevated in HCC biopsies compared with corresponding adjacent tissues, and positively correlated with serum α-fetoprotein, a clinical indicator of pathological progression. In searching chemicals targeting NRF2 for chemotherapy, we discovered that camptothecin is a potent NRF2 inhibitor. Camptothecin markedly suppressed NRF2 expression and transcriptional activity in different types of cancer cells including HepG2, SMMC-7721 and A549. As a result, camptothecin sensitised these cells to chemotherapeutic drugs in vitro and in xenografts. CONCLUSIONS: Camptothecin is a novel NRF2 inhibitor that may be repurposed in combination with other chemotherapeutics to enhance their efficacy in treating high NRF2-expressing cancers.